?CONDUCTIVITIES AND IONIC ASSOCIATION OF COPPER (II) AND MANGANESE (II) SULPHATES IN METHANOL + WATER AT 298.15 K - NIAZI, M. SADlQ KHAN (Biological Sciences - PJSIR, 1994)
Electrolytic conductivities for copper (IT) and manganese (II) sulphates in hinary mixtures of methanol +water have been measured at 298.15 K. The data were analyzed with the Lee and Wheaton conductivity equation for the derivation of limiting molar conductivities and association constants. TI;., results arc compared with those in the literature pertaining to analogous media, derived conductometrically.